FILSAFAT KEHENDAK SCHOPENHAUER DAN SIFAT QANA’AH SEBAGAI LANDASAN GAYA HIDUP MINIMALIS - Arifin, Jainul; Sofyan, Nurul Hikmah; Pujiono, Imam Prayogo (Academic Journal of Islamic Principles and Philosophy, 2024)
Consumerism often promises or measures one’s happiness through the ownership of things. In fact, the happiness obtained from material possessions is only temporary . This research aims to study how the theory of "abjuring willing” in Schopenhauer's philosophy and qana'ah in the perspective of Sufism can contribute to strengthening the basis of a minimalist lifestyle, the purpose to  provide a new life orientation for individuals who are bored with the cultural orientation of consumerism. This type of research is qualitative library research where in analyzing the researcher uses an integrative analysis method namely an analysis from a philosophical and Sufism perspective according to the theory offered by the author in this article. Data collection uses documentation techniques taken from sources relevant to the research focus. The finding of this research is that the theory of "abjuring willing” by Schopenhauer and qana'ah can be a basis for individuals to strengthen the implementation of a minimalist lifestyle. From the theory of " abjuring willing", individuals can learn to reduce the desire to have more. Meanwhile, by instilling qana'ah within oneself, individuals will feel satisfied with what they have.